2017
DOI: 10.1097/md.0000000000007763
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study investigating the correlation of diabetes mellitus with pleural empyema in adults in Taiwan

Abstract: We assessed the association between diabetes mellitus and the risk of pleural empyema in Taiwan.A population-based retrospective cohort study was conducted using the database of the Taiwan National Health Insurance Program. There were 28,802 subjects aged 20 to 84 years who were newly diagnosed with diabetes mellitus from 2000 to 2010 as the diabetes group and 114,916 randomly selected subjects without diabetes mellitus as the non-diabetes group. The diabetes group and the non-diabetes group were matched by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…It may be because our patient was having diabetes which has been shown independent risk factor in diabetes [9].…”
Section: Case Reportmentioning
confidence: 88%
See 1 more Smart Citation
“…It may be because our patient was having diabetes which has been shown independent risk factor in diabetes [9].…”
Section: Case Reportmentioning
confidence: 88%
“…Empyema following aspiration of a FB is rare scenario which has never been reported in literature in adults. One study which was done over a period of 15 year revealed among 1038 patients of bronchiectasis only eight were found to be due to a long retained FB [9]. It has been proven again and again that removal of FB is suffi cient to revert the lung changes to normal, and usually it does not warrant any surgical intervention but at times need lobectomy or even pneumectomy [10].…”
Section: Case Reportmentioning
confidence: 99%
“…Patients with diabetes mellitus were proven to have increased respiratory infectious risk due to inadequate clearance or the disturbance of normal pulmonary immune function [20]. It has been reported that diabetic patients conferred a 1.71-fold increased risk of empyema thoracis without any comorbidity [21]. A series of retrospective studies showed that the hazard of developing empyema was higher for patient with diabetes mellitus than those with chronic obstructive lung disease or chronic liver disease and cirrhosis [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…L'association entre l'incidence de la pneumonie communautaire et le diabète est retrouvée dans la plupart des études (mais pas toutes). Il est également lié à une augmentation de complications de cette pneumonie (bactériémie, empyème, décès) [22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Les Infections Respiratoires Bassesunclassified